Influencia de la temperatura de secado y calcinación en la preparación de hpw/SiO2 como catalizador para bioceldas - Contreras Sánchez, Jhancarlos Breiner (2018)
The influence of the drying and calcination temperature in the preparation of catalysts used in an electrochemical starch cell (biocell) was studied. The catalyst consisted of tungsten phosphoric acid (HPW) supported on a silicon oxide matrix. (SiO2) forming the "HPW/SiO2" system that when prepared at different drying temperatures (40°C, 60°C and 80°C) and calcined (350°C, 500°C and 650°C) achieved the impregnation of HPW in SiO2, which allowed heterogeneous catalysis in the biocell. In this way, the recovery of the catalyst was achieved after its first cycle of use and they were used in two additional cycles. The results show that the conditions in which the catalyst "HPW/SiO2" generates the highest average of voltages are when they are calcined at 500°C, temperature at which the HPW is impregnated much better. Also, these catalysts present better performance in the second and third cycle of use. It is demonstrated that it is possible to generate voltage in a starch biocell using supported tungsten phosphoric acid and that this can be recovered for use in different cycles which allows a better use of the voltage generation system